(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The empowerment of women has emerged as a crucial matter in India, as their exclusion from the development process is both unjust and incomplete. Despite comprising nearly 48.46% of the population, women’s participation in economic activities stands at a mere 34%. To enhance the status of women, it is imperative to empower them economically, politically, and socially. Microfinance has become a vital tool for empowering marginalized populations and plays a significant role in rural development. This paper explores the impact of microfinance and Self-Help Groups (SHGs) in reducing poverty, empowering women, and fostering sustainable national development. It also examines the pivotal role of SHGs in women’s financial inclusion and empowerment, while addressing barriers such as education and employment. Additionally, the paper highlights the need for increased initiatives, innovations, and interventions in the SHG sector to strengthen the development agenda.